Similitudes and singularities of higher education systems in the Mediterranean countries: Historical construction, policy and evolution of key indicators - Cláudia Urbano (REGION, 2019)
Higher education is one of the most important key values for changes in societies and exchanges among different societies. Analysing higher education systems in Europe, it is clear that Southern Europe has been determining many differences with the rest of the continent, despite the effort of the Bologna Process to ensure comparability in the standards and quality of higher education qualifications. Taking into account four Southern Europe countries - Portugal, Spain, Italy and Greece - and regarding their link to a certain Mediterranean culture, our proposal is to analyse these countries' higher education systems, their growth, using indicators on educational stock, economic growth and development, supply and demand of higher education and economic indicators relating training and the economy such as graduated employment rates. Also education public policies will be considered in the analysis as they interfere in higher education systems' trajectories. Comparing them we will be able to identify similitudes and singularities in these educational realities, leading us to conclude about the existence of a Southern European way of making higher education a specific value in Mediterranean culture. This topic is even more important as it may be related to the recent key focus of EU activities in Southern Mediterranean region. The Mediterranean Strategy for Sustainable Development (MSSD) recognises that education in the Mediterranean needs strengthening by introducing sustainable development, through a holistic approach, into educational curricula, from primary school right up to higher education. The search for synergies between higher education research and innovation in the Mediterranean area already started. With our post-doctoral research project focusing on higher education and its links to societies, educational policies and national economies, our goal is to share some questions and to contribute to the debate on higher education reinforcing and enriching sociological analysis on higher education between Mediterranean countries.
Keywords: 330